Improvement of the cryopreservation method for the Babesia gibsoni parasite by using commercial freezing media - Kusakisako, Kodai; Masatani, Tatsunori; Yada, Yurika; Talactac, Melbourne Rio; Hernandez, Emmanuel Pacia; Maeda, Hiroki; Mochizuki, Masami; Tanaka, Tetsuya (Parasitology international, 2016)
In vitro cultivation and cryopreservation under liquid nitrogen have already been reported and established for Babesia bovis and Babesia bigemina parasites. Although the in vitro cultivation methods for Babesia gibsoni have been reported and established, the cryopreservation methods for this parasite have not been established completely. In this paper, we compared several freezing media for the cryopreservation of B. gibsoni parasite. The CELLBANKER® series (1 plus and 2), STEM-CELLBANKER®, and CultureSure® were used for commercial freezing media; 10% dimethyl sulfoxide in 90% fetal bovine serum, 20% polyvinylpyrrolidone in phosphate-buffered saline (established for bovine Babesia parasites), and 28% glycerol supplemented with 3% sorbitol and 0.65% NaCl dissolved in water (established for Plasmodium parasites) were used for conventional media. Our results demonstrated that the CELLBANKER® series (1 plus and 2), STEM-CELLBANKER®, and CultureSure® are effective freezing media for B. gibsoni parasite compared to the cryopreservation methods of bovine Babesia and Plasmodium parasites. Our improved method of cryopreservation would contribute to the stability of the in vitro cultivation of B. gibsoni parasite. [Display omitted] •In B. gibsoni, CELLBANKER® series were the most effective freezing media.•STEM-CELLBANKER® and CultureSure® were better freezing media.•20% PVP and 28% glycerol+3% sorbitol+0.65% NaCl freezing media were ineffective.